Your sheep : a kids' guide to raising and showing - Simmons, Paula; Salsbury, Darrell L., 1936- (Pownal, Vt. : Storey Communications, 1992)
A guide to the choosing, handling, care, breeding, and showing of sheep.
"A Garden Way Publishing book."
Includes index.
Keywords: Sheep -- Juvenile literature; Sheep -- Showing -- Juvenile literature; Sheep